(untitled) (Global Journal of Medical Research, 2023)
In 95 (55 men and 40 women) representatives of the Uzbek population aged 18-30 with normal physiological bite, the frontal cephalogram parameters evaluating the relationship of the upper and lower jaws according to "Grummons" were determined. When determining the relationship of the upper and lower jaws, using the methods of determining the indicators of the development of the lower and upper jaws in the transverse and vertical directions proposed by the author, it was observed in the representatives of the Uzbek population. These indicators are used in the diagnosis and treatment of anomalies of the face and jaws, which are caused by the relation of the face and jaws.